"Unsustainable drugs" and intergenerational healthcare justice - Refolo, Pietro; Sacchini, Dario; Rumi, Filippo; Cicchetti, Americo; Spagnolo, Antonio G. (Medicina e Morale, 2019)
The recent introduction of new direct-acting antiviral drugs for the treatment of patients with hepatitis C that are extremely effective in treating the disease but that are associated with exorbitant costs raised public debate about healthcare distributive justice. The aim of this article is to provide a brief discussion on the topic of the so-called "unsustainable drugs" examined under a specific model of distributive justice, i.e. egalitarianism, and from an intergenerational perspective. The conclusion is that to date healthcare systems are facing the issue of sustainability through the optimization of pharmaceutical spending, but they are not well equipped to face the possibility of an inevitable divergence between demand and supply of this kind of drugs. The latter should be addressed with reference to the conception of distributive justice of a certain society, and in particular, to the amount of resources that a society wishes to pay for the treatment of one of its member. Finally, in terms of distributive justice, the argument - which is often supported by pharmacoeconomic evaluations - according to which the vast amount of money spent now for this type of drugs will allow to have savings in the long run is not in itself coherent with the main theories of justice. Considerations that are extrinsic to the assumptions of the main theories of justice are needed in order to justify the argument above.